W stronę etyki ekologicznej - Grzesica, Jan (Śląskie Studia Historyczno-Teologiczne, 1980)
This work concerns the most pressing — except war — danger for the world and mankind: the ecological disaster. The present author tries to define a theological and moral standpoint of the Church to this question, as seen in the light of such ecclesiastical papers as Constitution „Gaudium et Spes”, the document of the Third Synod of Bishops „Justice in The World”, The Apostolical Letter „Octogesima Adveniens”, Pope Paul's VI message to The Stockholm Conference for Protection of Natural Environment and others. It is the mankind's duty not only to avoid spoiling of the natural environment, but to shape it properly as well. This duty is a moral one and pertains to the problems of moral philosophy. Assuming that, author of this work presents us subsequently some principles of a kind of environmental ethics („eco-ethics”), the aim of which is to indicate, what should man do to protect the natural environment, and to say why should he do so. As the main source of threats for the natural environment Rev. Jan Grzesica considers the mentality of the contemporary man, his egoism and selfishness, his false hierarchy of values, according to which material goods are the most important — in spite of the order established by God, who indicates us the supernatural values and and the supreme aim as matters of the utmost importance. Man has been created by God as a being consisting both of the body and the spirit and as such he then has been redeemed by Our Lord Jesus Christ. Therefore it won't be enough to protect our world against an ecological disaster if we would clean the atmosphere, soil and water up and re-create the areas of silence only. First of all man must clear up himself and his mentality; he must define his place in the natural environment. Together with the man also the nature has been created by God as well and both constitute an inseparable unity, which is expecting salvation. That is why the mutual cooperation of both — the man and his environment — is necessary. God has submitted the earth to the man, but at the same time He has committed the earth to man's care. The foundation of eco-ethics is the precept of love. Our love towards God implies a deep esteem towards His work. The man's moral duty is a sort of an ecological asceticism — he should provide for his needs at the least possible consumption, trying to endeavour after an ethical, spiritual and cultural growth. The man's aim should be „to be”, not „to have”. A Christian, responsible for the world's shape and its future, does not stand in blind opposition to the progress, nevertheless he should stand in opposition against a blind progress. The limitations of human activity throughout the world are defined by the St. Franciscus' respect to nature. Nature is not „res nullius”, but it is „res omnium”. As a property of all mankind it belongs also to the future generation, because God is the Father of all people and He is the Donor of life for all of them.